Implementasi Strategi Pembelajaran Ekspositori dalam Meningkatkan Motivasi Belajar Peserta Didik di Dalam Kelas pada Mata Pelajaran PAI - Zakirul Nader; Hanifah Zahra Munawaroh; Gusmaneli Gusmaneli (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to analyze the implementation of expository strategies in improving the learning motivation of students in PAI (Islamic Religious Education) subject. The expository strategy is a teacher-centered learning approach that emphasizes the structured delivery of material, enabling students to understand concepts systematically and clearly. This research uses a qualitative descriptive method through classroom observation, interviews with teachers and students, and documentation studies. The results show that the implementation of expository strategies with a combination of explanation, question-and-answer, and reinforcement techniques is effective in increasing students’ learning motivation. Students show increased attentiveness, enthusiasm for participating, and better understanding of PAI material. It is concluded that expository strategies, when applied appropriately and interactively, can significantly improve learning motivation in PAI classrooms.